2010
DOI: 10.1158/1538-7445.am10-821
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 821: Plasma exosomes are a robust biosignature for prostate cancer

Abstract: We have developed a novel, versatile, multiplexed exosome-based diagnostic platform that can identify highly specific and sensitive disease biosignatures. This platform has been used to identify a plasma-based exosome biosignature for prostate cancer (PCa) that is superior to current tests, which rely on increased levels of either PSA in the blood or elevated levels of the PCA3 transcript in the urine. Unfortunately, PSA levels can also be elevated due to confounding conditions like benign prostate hyperplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Subsequent studies demonstrated the utility of exosomal DNAs for tumor molecular analysis, presenting them as reflective tumor markers [134,135]. Moreover, the various types of RNAs can also be used as reflective disease markers, since their levels or patterns showed a correlation with various types of cancer: exosomal miRNA in lung adenocarcinoma [136,137,138], pancreatic cancer [139], glioblastoma [93], melanoma [119],mRNA mutants (EGFRvIIImRNA) and miRNAs in glioblastomas [133], ovarian cancer [68], prostate cancer [140,141,142], and gastric cancer [143]. …”
Section: Microfluidic-based Approaches For Exosome Investigation Imentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies demonstrated the utility of exosomal DNAs for tumor molecular analysis, presenting them as reflective tumor markers [134,135]. Moreover, the various types of RNAs can also be used as reflective disease markers, since their levels or patterns showed a correlation with various types of cancer: exosomal miRNA in lung adenocarcinoma [136,137,138], pancreatic cancer [139], glioblastoma [93], melanoma [119],mRNA mutants (EGFRvIIImRNA) and miRNAs in glioblastomas [133], ovarian cancer [68], prostate cancer [140,141,142], and gastric cancer [143]. …”
Section: Microfluidic-based Approaches For Exosome Investigation Imentioning
confidence: 99%
“…mRNA mutants (EGFRvIIImRNA) and miRNAs in glioblastomas [133], ovarian cancer [68], prostate cancer [140,141,142], and gastric cancer [143].…”
Section: Microfluidic-based Approaches For Exosome Investigation Imentioning
confidence: 99%
See 1 more Smart Citation